Is click chemistry attractive for separation sciences?. Issue 13 (29th May 2013) - Marechal, Audrey; El‐Debs, Racha; Dugas, Vincent; Demesmay, Claire
Abstract : Trends in LC focus on dedicated separation developments spanning different fields of applications ranging from sample preparation to miniaturization. Chromatographic performances result from the porous media, its implantation inside the "column, " and its surface functionalization. Because molecular interactions govern chromatographic phenomena, surface functionalization is still a hot research topic. Besides standard approaches for surface functionalization, the use of new surface chemistry reactions opens new perspectives. Click chemistry belongs to this new class of chemical reactions, characterized by its specificity, compatibility with aqueous media, and high reaction yields. In this frame, we review the use of click chemistry reactions in chromatographic sciences. In a first part, we present click chemistry with a specific focus on its implementation in stationary phases. The use of these new clicked materials is detailed and discussed with respect to the chromatographic mode.